Proteomic Biomarkers for Occupational Secondhand Smoke Exposure - Neves, Sofia (2020)
A Global Health Problem: Smoking kills more than 7 million people/year worldwide; More than 890,000 are deaths resulting from exposure to Second Hand Smoke (SHS); In adults, SHS is associated to cardiovascular and respiratory diseases, including coronary heart disease and lung cancer.